Recovery-stress states of professional ballet dancers during different phases of a ballet season - De Wet, J. S.; Africa, E.; Venter, R. (Journal of Dance Medicine & Science, 2022)
Ballet dancers are exposed to chronic high training and performance demands that are associated with overtraining syndrome and injury. Balancing high training loads with recovery to reduce the risk of negative training adaptations is critical. Moreover, the recovery-stress states of professional ballet dancers during training phases of a season are largely unknown. Professional dancers (n = 27) from one classical ballet company in South Africa were monitored for two 8-week phases of a ballet season. A recovery-stress questionnaire for Athletes (RESTQ-76 Sport) was completed weekly during the rehearsal phase (P1) and the performance phase (P2), which took place at the start and the end of the ballet season, respectively. Comparisons were calculated between phases, sexes, and levels of performance with a mixed-model ANOVA and between demographic variables with a one-way ANOVA. The performance phase was signified by lower total recovery (TR, p < 0.01) and higher total stress (TS, p < 0.01) for the group. Female dancers had significantly lower recovery scores than male dancers during P2 (p < 0.01). No differences between levels of performance were found. Subscales previously associated with overreaching and injury were identified in certain groups during P2. In conclusion, P2 was a critical period where dancers, especially females, experienced high stress and low recovery. Tis could increase the risk for injury and negative training adaptations.